2020
DOI: 10.1002/cncr.32769
|View full text |Cite
|
Sign up to set email alerts
|

Significance of minimal residual disease monitoring by real‐time quantitative polymerase chain reaction in core binding factor acute myeloid leukemia for transplantation outcomes

Abstract: Background Despite the well‐defined role of minimal residual disease (MRD) monitoring by real‐time quantitative polymerase chain reaction (RT‐PCR) for RUNX1/RUNX1T1 and CBFB‐MYH11 transcripts in core binding factor (CBF) acute myeloid leukemia (AML) after intensive chemotherapy, there has been a paucity of data assessing the utility of MRD monitoring at and after allogeneic hematopoietic stem cell transplantation (HSCT). Methods Patients with CBF AML who underwent HSCT in complete remission (first or second) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 29 publications
2
14
0
Order By: Relevance
“…One possible explanation lies in biologic mechanisms of a somewhat immunosurveillance effect in preventing disease reappearance, similar to what is documented in the allotransplant setting, that might lead up to the clearance of leukemic compartment, as suggested by the progressive decline of MRD documented, in a timeframe up to 16 months, after consolidation, in some patients without further treatment [62,75,94]. Those findings reinforce the caveat that patients with low molecular burden of disease may need close monitoring, instead of urgent intervention [95]. The recent observation of CBFB-MYH11-specific T cells indicates that CBFB-MYH11 fusion neoantigen is naturally processed and presented on AML blasts and enables T cell recognition and the killing of leukemic cells, supporting the hypothesis of a potential contribution of specific cytotoxic cells in MRD control and CCR maintenance [96].…”
Section: And After the End Of Treatmentsupporting
confidence: 63%
See 1 more Smart Citation
“…One possible explanation lies in biologic mechanisms of a somewhat immunosurveillance effect in preventing disease reappearance, similar to what is documented in the allotransplant setting, that might lead up to the clearance of leukemic compartment, as suggested by the progressive decline of MRD documented, in a timeframe up to 16 months, after consolidation, in some patients without further treatment [62,75,94]. Those findings reinforce the caveat that patients with low molecular burden of disease may need close monitoring, instead of urgent intervention [95]. The recent observation of CBFB-MYH11-specific T cells indicates that CBFB-MYH11 fusion neoantigen is naturally processed and presented on AML blasts and enables T cell recognition and the killing of leukemic cells, supporting the hypothesis of a potential contribution of specific cytotoxic cells in MRD control and CCR maintenance [96].…”
Section: And After the End Of Treatmentsupporting
confidence: 63%
“…To reiterate the relative significance of positive MRD pre SCT, Zhao et al [109] reported that instead of MRD before SCT, the unfavorable effect on prognosis in multivariate analysis is attributed to detectable MRD post haploidentical SCT, without the necessity of further intensive chemotherapy for MRD-positive patients prior to transplantation. Yalniz et al [95] showed that there is no impact of the MRD level by qRT-PCR on the relapse incidence, even in the patients with the highest disease burden. In addition, in this study, two MRD checkpoints post SCT were identified: the presence of MRD on day +30 did not indicate impending relapse, whereas patients who had detectable disease on day +100 had a 3-year relapse incidence of 27.6% versus 9.7% for patients without residual disease, although not reaching statistical significance.…”
Section: Mrd Should Be Assessed Pre Transplant Mrd Should Be Performed Post Transplantmentioning
confidence: 99%
“…Therefore, further therapy stratification after CR would be necessary to identify the optimal PRT choice. MRD has been effectively used for directing PRT [ 7 , 19 , 23 , 36 38 ]. Nevertheless, the best timing for treatment choice based on MRD remains inconclusive [ 19 , 23 , 24 , 34 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…8,27,49 Molecular MRD monitoring after allogeneic SCT While there is mounting evidence on the role of molecular MRD monitoring after completion of intensive chemotherapy, data are scarce on the clinical utility of serial qPCR MRD PB sampling in the post-transplant setting in CBF-AML because most reports are based on BM monitoring. [57][58][59][60] Longitudinal MRD sampling after SCT may contribute to optimisation of treatment strategies, e.g. tapering of immunosuppression or donor lymphocyte infusions in the event of rising transcript levels and the current ELN MRD guidelines recommend MRD testing both before and after SCT.…”
Section: Correlation Between Paired Bm and Pb Qpcr Mrdmentioning
confidence: 99%